Multiscale effects on freshwater fish distribution in a highly disturbed Mediterranean-type basin: community-level and species-level responses - P. Sáez-Gómez; A. Ramos-Merchante; J. Prenda (Aquatic Ecology, 2020)

Freshwater ostracods as environmental tracers - F. Ruiz; M. Abad; A. M. Bodergat; P. Carbonel; J. Rodríguez-Lázaro; M. L. González-Regalado; A. Toscano; E. X. García; J. Prenda (International Journal of Environmental Science and Technology, 2013)

Identifying priority sites for the conservation of freshwater fish biodiversity in a Mediterranean basin with a high degree of threatened endemics - V. Hermoso; S. Linke; J. Prenda (Hydrobiologia, 2009)

Ecological traits of fish assemblages from Mediterranean Europe and their responses to human disturbance - T. FERREIRA; J. OLIVEIRA; N. CAIOLA; A. DE SOSTOA; F. CASALS; R. CORTES; A. ECONOMOU; S. ZOGARIS; D. GARCIA‐JALON; M. ILHÉU; F. MARTINEZ‐CAPEL; D. PONT; et al. (Fisheries Management and Ecology, 2007)
Mediterranean river systems are characterised by more diverse fish assemblages and regional ecological processes compared with the rest of Europe. A data set from Mediterranean France, Iberia and Greece (∼2000 sites) was used to describe the characteristics of fish assemblages, explore their responses to anthropogenic disturbance and analyse the implications for river quality assessment. There was a southwards decline in species richness per site, but endemicity and proportion of alien species increased. Sites in the eastern Mediterranean had higher endemicity, lower site richness and lower number of alien species than sites in western Mediterranean Europe. Assemblage composition differed between Mediterranean sub‐regions, but was dominated by three major fish types: a salmonid fish type common throughout the study area and two cyprinid‐dominated fish types (in some sub‐regions, Salmo trutta L. is present but not numerically dominant), corresponding to a gradient in hydrological and temperature regimes. Metric responses to perturbation were compared with those found at the European (larger scale) and basin (smaller scale) levels. Overall metric response was weaker in this Mediterranean application. The best responses to human pressure were usually obtained with abundance‐based metrics and included the contribution of naturalised alien species. Some widespread alien species contributed to the response to anthropogenic alteration (notably Cyprinus carpio L. and Lepomis gibbosus (L.)).

Size‐related and diel variations in microhabitat use of three endangered small fishes in a Mediterranean coastal stream - M. Clavero; F. Blanco‐Garrido; L. Zamora; J. Prenda (Journal of Fish Biology, 2005)
This study analysed the microhabitat use of three endangered fish species, Andalusian toothcarp Aphanius baeticus , Iberian loach Cobitis paludica and sand smelt Atherina boyeri , in a coastal stream stretch. Plastic minnow traps were set both during daytime and at night on the bottom and at the surface. Depth and presence of effective refuge were recorded for each trap. To assess size‐related changes in microhabitat use individuals of each species were classified in three size classes. The three species preferentially used bottom positions in the water column, though this behaviour was more evident in the case of Iberian loach. While large Iberian loach remained active at night Andalusian toothcarp and sand smelt were strongly diurnal, especially larger individuals. The three species showed a clear ontogenetic change in microhabitat preferences towards deeper waters. Small Andalusian toothcarp and medium‐sized Iberian loach used deeper microhabitat in the presence of refuge. Large Andalusian toothcarp consistently preferred exposed microhabitat at any time. Andalusian toothcarp using refuge were smaller at any time, while Iberian loach followed this pattern only at night. The differential vulnerability of these species to different predators (aerial and aquatic; diurnal and nocturnal) could explain the observed patterns in microhabitat use. Fish tended to co‐occur in microhabitats either due to habitat characteristics independently of species or due to species independently of habitat. Andalusian toothcarp segregated spatio‐temporally from sand smelt and Iberian loach, but these species occurred independently of each other. According to these co‐occurrence patterns, Andalusian toothcarp would be more sensitive than Iberian loach or sand smelt to interspecific interactions.

Habitat use by the fish assemblages of two chalk streams - J. Prenda; P. D. Armitage; A. Grayston (Journal of Fish Biology, 1997)
Patterns of habitat use by fish assemblages in two chalk streams in southern England were examined to identify species preferences with respect to major habitat gradients. Both study sites, although differing in some physical habitat characteristics, mainly channel width, water temperature and instream cover, could be arranged similarly along a continuum extending from erosional to depositional habitats. Twelve fish species were collected from stream surveys conducted during July 1993. The habitat was partitioned into six fish species associations that could be assigned to three habitat guilds: depositional ( Barbatula barbatula, Gasterosteus aculeatus and Anguilla anguilla ), riffle ( Leuciscus leuciscus, Thymallus thymallus and Salmo salar ) and generalist ( Salmo trutta, Phoxinus phoxinus, Gobio gobio, Cottus gobio, Lampetra planeri and Pleuronectes flesus ). At low to moderate densities the different species associations were collected in the same habitat patch, but at higher densities there was a clear tendency to mutual avoidance. In particular, large trout appeared as strong interactors that tended to exclude other species from their territories. It is hypothesized that the fish assemblage of the Mill Stream and Bere Stream have partitioned the habitat in such a way as to minimize potential Competition.